O rusycyzmach w utworach Mariusza Wilka (rekonesans badawczy) - Sarnowski, Michał (Studia Rossica Posnaniensia, 2021)
The article presents a survey of numerous Russian elements (lexemes and grammatical constructions) in the works of Mariusz Wilk in an attempt to provide their initial classification and interpretation. Mariusz Wilk, a Polish writer who lives and works in the Russian North, constantly weaves Russicisms into the tissue of his erudite and intertextual statements, making his texts a linguistic experiment with specific textual features. Out of two works by Wilk (Wołoka, Lotem gęsi), more than 140 lexical units (of different status) have been excerpted and subjected to a multifarious analysis. Their typology is based on the concept of space, which is one of the key categories of geopoetics. The author of the article claims that the Russian material in the studied works cannot be treated merely as Russicims in their strict lexicological sense because these words perform specific functions in the texts, among which the communicative, artistic and conceptual functions are in the foreground. Russian segments belong to the most important ingredients of the writer’s idiolect (idiostyle) and, therefore, they should not be treated solely as a violation of the lexical norm. The postulated qualitative and quantitative analysis of Russicisms in Wilk’s works, as well as the assessment of their functional load, open up new possibilities of viewing Russian-Polish language contacts not only as mutual interactions, but above all as building blocks of the author’s message, intersemiotic in its nature.